PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDS METHODIST BALAM - Lampita Siregar; Eddy Noviana; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the low learning outcomes of fourth grade PKn students in SDS Methodist Balam academic year 2016/2017. Initial data received by the researcher, from 23 students who reached the value of KKM only 10 students (43%) with an average of 64.26. This research is a classroom action research conducted collaboratively and participatively in collaboration with science teacher of class IV in SDS Methodist Balam. The instrument of this research consists of learning device used in this research based on Education Unit Level Curriculum (KTSP). Learning tools consist of syllabus, lesson plans, student worksheets and observation sheets. The result of research got the activity of teacher at first cycle of meeting I that is 58,65% with good category, second cycle meeting to I that is 80,91% with good category. At cycle II meeting 1 that is 89,84% with very good category and second meeting second cycle that is 98,20% with very good category. Then the percentage of first cycle activity of the first student is 48,93% with enough category, at the second meeting of cycle I that is 74,88% with good category. In the second cycle of meeting I is 89.81% with very good category, and the second meeting is 96.20% with very good category. As for the result of student learning that complete before held action only 10 student (43%) with average value 64,26. In the daily test I cycle I the number of completed students increased to 16 students or (69,5%) with an average score of 72.17. Furthermore, in II repetition cycle II increased again with the total number of students who complete as many as 19 students or (82,6%) with an average value of 79.13. The increase that occurred on student learning outcomes between the basic score of one cycle with the percentage of 13.10% and between the basic score of the second cycle with the percentage of 39.20%. This means that the classical value obtained by students has been above the established KKM.Keywords: Cooperative Learning Model Snowball Throwing, Learning Outcomes Pkn